'Like a bee's sting or a bullet': eroticism, violence and the afterlives of colonial romance in Medbh McGuckian's The Flower Master and Other Poems (1993). Issue 8 (3rd August 2022) - Garden, Alison
ABSTRACT: Throughout Irish history - and especially in the years immediately following the Act of Union and the later 'Troubles' at the end of the twentieth century - writers have turned to the narrative of lovers from 'across the divide', in multiple permutations, to explore the complexities of the Anglo-Irish relationship. This article will focus on The Flower Master and Other Poems (1993), an early collection from the contemporary Belfast poet Medbh McGuckain. In explicating how a select number of these poems engaged with sexual intimacy, conflict, the afterlives of Seamus Heaney and the colonial romance trope, this article will elucidate how McGuckian's work is charged with a particular erotic energy. In The Flower Master, sexuality develops in the shadow of a complex history and contemporary political contexts, creating a poetics that writes the province's Troubled past as intimately interwoven with the pairing of sex, desire, and violent conflict. Ultimately, this article argues that McGuckian plays with the representational possibilities offered to her through the rhetoric of the colonial romance trope, suggesting that sexual desire itself is conditioned by the political conditions that shaped the province's difficult history.